The etiologies and prognosis associated with spinal cord infarction - Hsu, Jung Lung (Ann Clin Transl Neurol, 2019)
BACKGROUND: This study aims to investigate the etiology and prognosis of spinal cord infarction (SCI). METHODS: Over a period of 16 years, we retrospectively analyzed 31 patients with SCI. Demographic features and symptom presentations were carefully documented. Etiology‐specific MRI features, such as the length and distribution of the lesions and owl’s eyes sign, were recorded and analyzed to determine their associations with the clinical signs/symptoms. RESULTS: In total, seven patients had aortic or vertebral artery dissections. We divided the patients with SCI into two groups: those with or without vessel dissection. Among SCI patients, the onset age was younger, and the proportion of patients with long‐segment lesions and posterior pattern involvement on axial view was higher in the group with dissection than in the group without dissection (all P < 0.05). The lesions were frequently located in the upper cervical or lower thoracic‐lumbar regions, and the lengths of the lesions were associated with 1‐month outcomes, suggesting that artery dissection may contribute to the longitudinal and posterior extension of SCI. In contrast, among patients without dissection, the range of longitudinal extensions of in spans of vertebral bodies was broader (range, 1–8). A higher proportion of patients had focal pain adjacent to the lesion (P = 0.05) and a poorer 1‐month outcome (P = 0.04) in the long‐segment lesion group than in the short‐segment lesion group. CONCLUSIONS: A detailed history and the use of modern imaging tools may help clinicians search for vessel dissection and other etiologies, evaluate the spatial extension of lesions in SCI, and predict prognosis.